Late-Season Nitrogen Fertilizer Application in Soybean - D. R. Hodgins; E. A. Adee; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2015)
Field experiments were conducted at the Kansas River Valley Experiment Field, located near Rossville and Topeka, KS, in the summer of 2014 to evaluate effects of late-season nitrogen (N) fertilizer application on modern soybean genotypes. A unique fertilizer N source (urea) was applied at five N rates (0, 40, 80, 120, and 160 lb N/a) to soybean at the R3 growth stage. The main objective was to determine if late-season N application has an agronomical benefit to soybean producers. Overall soybean yields ranged from 43.7 to 57.5 bu/a considering both experimental fields. At Rossville, sudden death syndrome (SDS) affected the final soybean yield potential. Application of late-season N fertilizer did not significantly increase soybean yields at the evaluated sites. Maximum soybean yields, 46 bu/a at Rossville and 57 bu/a at Topeka, were documented at the 0-N fertilizer rate.
Keywords: soybean; late-season nitrogen fertilizer; yield